On dr. Claudio Gutierréz Carranza's thought: An algorithm of Artificial Inteligence to prove theorems of uniform cuantification logic - Rojas Romero, José Ángel (2025)
In addition to an overview of Claudio Gutiérrez's philosophical thought, this article presents an application of an algorithm for automatic theorem proof that was carried out as part of the Logic and Cybernetics course, taught by Claudio Gutiérrez in 1971 and whose purpose of application was to prove the theorem called Holiday Venture. Gutiérrez, in An Artificial Intelligence Algorithm, describes the aforementioned algorithm with three variants, but one of those variants, called Empirical Orientation, was not implemented in a program. This article shows the application of this variant.